Studies toward bivalent κ opioids derived from salvinorin A: heteromethylation of the furan ring reduces affinity - Munro, Thomas A.; Xu, Wei; Ho, Douglas M.; Liu-Chen, Lee-Yuan; Cohen, Bruce M. (Beilstein Journal of Organic Chemistry, 2013)
The recent crystal structure of the κ-opioid receptor (κ-OR) revealed, unexpectedly, that the antagonist JDTic is a bivalent ligand: in addition to the orthosteric pocket occupied by morphinans, JDTic also occupies a distinct (allotopic) pocket. Mutagenesis data suggest that salvinorin A (1) also binds to this allotopic pocket, adjacent to the aspartate residue that anchors the basic nitrogen atom of classical opiates (Asp138). It has been suggested that an H-bond donor appended to 1 might interact with Asp138, increasing affinity. Such a bivalent ligand might also possess altered functional selectivity. Based on modeling and known N-furanylmethyl opioid antagonists, we appended H-bond donors to the furan ring of 1. (Dimethylamino)methyl groups at C-15 or C-16 abolished affinity for κ-OR. Hydroxymethylation at C-16 was tolerated, but 15,16-bis-hydroxymethylation was not. Since allosteric modulators may go undetected in binding assays, we also tested these and other low-affinity derivatives of 1 for allosteric modulation of dynorphin A in the [35S]GTPγS assay. No modulation was detected. As an alternative attachment point for bivalent derivatives, we prepared the 2-(hydroxyethoxy)methyl ether, which retained high affinity for κ-OR. We discuss alternative design strategies for linked, fused or merged bivalent derivatives of 1.
Keywords: allotopic; bivalent ligand; designed multiple ligand; JDTic; κ-opioid receptor; natural products; Salvinorin A